Entre a cultura e a política: uma geografia dos "currais" no sertão do Seridó Potiguar - Azevedo, Francisco Fransualdo de (2007)
All and any social relationship usually involves relationships of power, consequently, political relationships. Politics, in the wide meaning of the term, is responsible, or at least explains good part of the social and political global contemporary conjuncture. In Brazil, it is directly related to the cultural framework constituted by Afro-Iberian-Indian symbolic representations. In the Northeast, the conservative political relationships, although backed by the effective political culture, impede wider and more effective social improvements. This research, which conceptual basis is orientated towards the political-cultural approach, seeks, mainly, to understand the existent relationship between culture and politics in the Potiguar Seridó area, trying to identify and to explain the " new " manipulation instruments and, at the same time, the social agents control and political-family groups, based in some actions of the State, with prominence for the social programs. The references inventoried in the theoretical framework, the wide rising of secondary data as well as the information obtained through the empiric research made possible the realization and the refinement of this analysis. Some main lines lead the undertaken analysis: one concerns the recognition of the culture while social capital, therefore, while element capable to elevate the quality of life of populations allocated in geographical areas, as it is the case of the Seridó; other refers to that same culture, politics, especially, it is capable to back at the stage of the relationships of power, impeding, or at least limiting, the social development with " individual freedom " and social groups; another line suggests changes and proposes alternative models, even if that demands more time to execute, but that certainly will bring positive transformations for the society. This paper still seeks to add knowledge on the studied area, Seridó, as well as to contribute to the studies concerning culture and politics, taking into consideration the economical and social relationships, in the ambit of Geography and of other social sciences.